Analisis Ketersediaan Dan Aksesibilitas Layanan Kesehatan Di Nagari Pasilihan Untuk Meningkatkan Kesejahteraan Masyarakat - Atika Zata Amani; Dwita Adinda Yusri; Fikry Zaldi; Winda Kusuma Wardani; Yuni Nuril Putri; Linda Rosalina (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This study aims to analyze the availability and accessibility of healthcare services in Nagari Pasilihan, X Koto Diatas Subdistrict, Solok Regency, and their impact on community welfare. Although basic health facilities such as Poskesri, Pustu, and Puskesmas are present, service quality remains hindered by various structural issues including limited medical personnel, outdated equipment, and non-digital medical records. Geographic isolation and poor road infrastructure further restrict access, particularly for low-income residents. Employing a descriptive qualitative approach, the study reveals a gap between the physical availability of health services and their optimal utilization. The findings are expected to contribute to the development of more inclusive, locally-driven rural health policies.